Feeding ecology of tiger fish, (Hydrocynus vittatus) in the Kalimbeza Channel on the Zambezi River, Namibia - Simasiku EK; Mafwila SK; Abah J; Hay CJ; Matengu KK (International Journal of Life Sciences, 2017)
The feeding ecology of tiger fish, Hydrocynus vittatus (Characidae), in the Kalimbeza Channel on the Zambezi River, Namibia was investigated between February - December 2016. The fish sampling was conducted monthly using cotton multifilament nets with stretched mesh sizes: 12, 16, 22, 28, 35, 45, 57, 73, 93, 118 and 150 mm. A total of 498 specimens of the fish were collected and their stomachs dissected for contents analyses. The findings indicated that large size classes of H. vittatus (>176mm) were largely piscivorous, and showed a diet shift with changes in size. The small size classes of H. vittatus (<140mm) consumed mainly Aquatic insects (21.1%), Synodontis spp (17.8%), and Micralestes acutidens (12.1%). They later shifted to diet in which Synodontis spp (26.1%), Brycinus lateralis (15.2%) and M. acutidens (13.0%) dominated. Seasonal shift in diet were apparent due to changes in seasonal food abundances and distributions. During the wet season, H. vittatus fed mainly on aquatic insects and later showed a shift to diet dominated by fish prey items during the dry season. Hydrocynus vittatus showed no strict food regime and this gives it a better chance of survival. Ratios of prey length-predator length averaged approximately 0.27. The study showed that H. vittatus plays an ecological role with the ability of converting un-exploitable non-commercial species into exploitable protein. Hence their population must be of conservation priority to ensure a balanced fishery in the Zambezi River.